Sex Hormones and the QT Interval: A Review - Sedlak, Tara (Mary Ann Liebert, Inc., 2012)
A prolonged QT interval is a marker for an increased risk of ventricular tachyarrhythmias. Both endogenous and exogenous sex hormones have been shown to affect the QT interval. Endogenous testosterone and progesterone shorten the action potential, and estrogen lengthens the QT interval. During a single menstrual cycle, progesterone levels, but not estrogen levels, have the dominant effect on ventricular repolarization in women. Studies of menopausal hormone therapy (MHT) in the form of estrogen-alone therapy (ET) and estrogen plus progesterone therapy (EPT) have suggested a counterbalancing effect of exogenous estrogen and progesterone on the QT. Specifically, ET lengthens the QT, whereas EPT has no effect. To date, there are no studies on oral contraception (OC) and the QT interval, and future research is needed. This review outlines the current literature on sex hormones and QT interval, including the endogenous effects of estrogen, progesterone, and testosterone and the exogenous effects of estrogen and progesterone therapy in the forms of MHT and hormone contraception. Further, we review the potential mechanisms and pathophysiology of sex hormones on the QT interval.